ΞΕΝΟΙ ΘΙΑΣΟΙ ΣΤΗΝ ΟΘΩΜΑΝΙΚΗ ΘΕΣΣΑΛΟΝΙΚΗ, 1870-1912 [FOREIGN THEATRE COMPANIES IN OTTOMAN THESSALONIKI, 1870–1912] - Pallikari, Olivia (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This article examines the activities of foreign touring theatre companies in Ottoman Thessaloniki between 1870 and 1912. This period is significant for two reasons: it represents a largely unexplored chapter in the city’s theatrical history and marks the beginning of a systematic theatrical movement from 1870 onwards. The study concludes in 1912, the year Thessaloniki was incorporated into the modern Greek state, when performances by foreign companies declined due to political changes. The article aims to outline the conditions under which foreign performances were staged and identify the factors that made Thessaloniki a key stop for touring troupes. Additionally, it seeks to provide a detailed account of the diverse ethnic companies that performed in the city's theatres, examining their theatrical selections and repertoire. This comprehensive analysis offers a broader understanding of the theatrical landscape presented by foreign companies in Ottoman Thessaloniki.